ANALYSIS OF POTENTIAL HAZARDS FOR WORK ACCIDENTS USING THE HIRA (HAZARD IDENTIFICATION AND RISK ASSESSMENT) METHOD ON GOLD MINE WORKERS IN EAST SUWAWA DISTRICT - Siti Ismi Cahyani Ismail; Irwan Irwan; Nur Ayini S. Lalu (Gorontalo State University, 2023)
Kecelakaan kerja dapat dicegah dengan menganalisis identifikasi sumber bahaya yang ada di tempat kerja dan penilaian tingkat resikonya. HIRA adalah serangkaian proses mengidentifikasi bahaya yang dapat terjadi dalam aktivitas rutin ataupun non rutin. Kebaruan penelitian ini karena meneliti tentang bahaya terhadap kecelakaan kerja menggunakan metode HIRA (Hazaard Identification And Risk Assesment). Tujuan Penelitian untuk menganalisis Potensi Bahaya dan Penilaian Risiko terhadap kecelakaan kerja dengan metode HIRA pada Pekerja Tambang Emas. Desain Penelitian Kuantitatif dengan sampel yang dibutuhkan dalam penelitian ini adalah 100 Responden. Analisis data menggunakan Analisis univariat untuk indikator identifikasi bahaya, penilaian risiko. Hasil penelitian menunjukan bahwa setiap pekerjaan di Tambang Emas berpotensi bahaya terdiri dari bahaya mekanis, fisik dan kimia. Terdapat 2 risiko termasuk kategori Very High, 7 risiko termasuk kategori Priority 3, 2 risiko temasuk kategori 1, 9 risiko termasuk kategori Acceptable dan 12 risiko termasuk kategori Substantial. Kesimpulan terdapat Potensi Bahaya di area kerja Tambang Emas Suwawa Timur jenis potensi bahaya seperti bahaya mekanis, Potensi bahaya Fisik dan Potensi bahaya kimia. Kata kunci: Bahaya; HIRA; K3; Risiko; Tambang Emas. Abstract Work accidents can be prevented by analyzing the identification of sources of hazards present in the workplace and an assessment of the level of risk. The novelty of this research is that it examines the dangers of work accidents using the HIRA (Hazard Identification And Risk Assessment) method. HIRA is a series of processes to identify hazards in routine or non-routine activities. The purpose of the study is to analyze potential hazards and risk assessments of work accidents using the HIRA method in Gold Mine Workers. The quantitative Research Design with the sample needed in this study is 100 Respondents. Data analysis using univariate analysis for hazard identification indicators and risk assessment. The results showed that every work in the Gold Mine has the potential to be hazardous, consisting of mechanical, physical, and chemical hazards. There are 2 risks, including the Very High category, 7 risks, including the Priority 3 category. 2 risks, including category 1. 9 risks, including the Acceptable type—and 12 risks, including a substantial variety. Conclusion There is a Potential Hazards in the East Suwawa Gold Mine work area types of potential hazards such as mechanical hazards, Potential Physical hazards, and Potential chemical hazards. Keywords: Danger; HIRA; K3; Risk; Gold mine.